CP-014 Impact of discharge pharmaceutical counselling on patient adherence to anti-infective treatment. (14th February 2016) - Salomon, L; Bordes, C; Leguelinel-Blache, G; Poujol, H; Kinowski, JM; Sotto, A; Faure, H
Abstract : Background: For years, bacterial resistance can affect the effectiveness of anti-infective treatment. Non-adherence is one of the factors responsible for the development of resistance that results in treatment failures, deaths and additional costs. Several activities could improve patient adherence, one of which is discharge pharmaceutical counselling (DPC). Purpose: The aim of the study was to assess the impact of DPC on adherence to anti-infective treatment prescribed for acute infection, as well as the patient's understanding and knowledge about his treatment. Material and methods: A prospective, single centre, interventional study was performed in a unit of infectious and tropical diseases, from November 2014 to July 2015. Patients were randomised to one of two groups: a control group which did not benefit from DPC and an interventional group which benefitted from DPC. The patient's adherence to anti-infective treatment was assessed indirectly by telephone contact with the community pharmacist and the patient. During the patient's interview, a quiz was used to assess understanding and knowledge of the treatment. Results: After 33 weeks, 89 patients were enrolled in the study, of whom 45 were in the interventional group. Median age was 64 (44; 76) years and the proportion of men was 53.9%. Finally, 49.4% of patients were non-adherent: 61.4% in the control group versus 37.8% in the interventional group (p < 0.05). In the interventional group, only 6.7% of patients involuntarily omitted at least a drug intake versus 31.8% in the control group (p < 0.01). DPC seemed to improve knowledge of anti-infective treatment (increase of 1 point in the quiz score; p = 0.052). Indeed, patients were more aware of side effects when they had DPC (25% in the control group vs 64.4% in the interventional group; p < 0.0005). Conclusion: DPC halved the rate of non-adherence, reducing involuntarily drug omission and improving patient's knowledge to anti-infective treatment, including knowledge of side effects. Thus it would be interesting to extend this practice to other healthcare units. In order to optimise clinical pharmacy activities, identification of risk factors for non-adherence should help to develop DPC by targeting patients at risk of non-adherence. No conflict of interest.